THE ROLE OF METACOGNITIVE AWARENESS IN ENHANCING PRODUCTIVE SPEECH SKILL ASSESSMENTS FOR ENGLISH LEARNERS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article explores the role of metacognitive awareness learners' understanding and regulation of their own cognitive processes in enhancing the assessment of productive speech skills for English learners. Metacognitive strategies, such as self-monitoring, self-evaluation, and goal-setting, enable learners to reflect on their language use, identify areas for improvement, and adapt their learning approaches.